HYDROCHEMISTRY OF LOWLANDS WATER OF SOUTHWEST BANGLADESH - Muhammad Qumrul Hassan (Lowland Technology International, 2000)
The paper presents the physical properties and chemical constituents of surface and groundwater of southwest lowland area. Annual seasonal and tidal flooding are the common phenomenon in lowland of Bangladesh. Monson climatic condition is the main responsible for the flooding both from onshore to offshore areas. These physical processes, the regional hydraulic head declination during the dry period (November-April) and some man-made activities have caused the present deterioration of water quality from the acceptable limit for conjunctive use of the area. Physico-chemical analyses of water from river and groundwater have revealed that EC, TDS, TH, Na+, CT are higher concentration levels then the standard limit. In thois context, many studies on water quality have revealed that the surface water of southwestern lowland is of primary salinity type, which can be found in the every dry period. Observation shows that the salinity level normally decreases when the high stream flow discharges from the upstream rivers during the very wet periods.